An Intelligent agent based Track-Before-Detect system applied to a range and velocity ambiguous radar - Hughes, Evan J.; Lewis, Michael B. (Cranfield University, 2009)
The problems associated with detecting low observable targets using Track-before-Detect systems based on Hough transform or Dynamic Programming techniques are reviewed. An alternative self-adaptive spatio-temporal CFAR system and a multiple hypothesis tracker based on Multiple Intelligent Software Agents and its adaptation to range and velocity ambiguous radar is described.
1st EMRS DTC Technical Conference – Edinburgh 2004